ความเสี่ยงต่อสุขภาพในการทำงานของแรงงานนอกระบบในชุมชนมุสลิม:กรณีศึกษาเทศบาลตำบลบางปู อำเภอยะหริ่ง จังหวัดปัตตานี (HEALTH RISK IN WORKING OF THE INFORMAL WORKERS IN MUSLIM COMMUNITY: CASE STUDY OF BANGPOO MUNICIPALITY, YARING DISTRICT, PHATTHANI PROVINCE) - แวหะยี, อุสมาน; คงทอง, พัทธนันท์ (วารสารมหาวิทยาลัยศรีนครินทรวิโรฒ สาขาวิทยาศาสตร์และเทคโนโลยี, 2011)
การวิจัยครั้งนี้เป็นการวิจัยเชิงพรรณนาแบบตัดขวาง มีวัตถุประสงค์เพื่อประเมินความเสี่ยงทางสุขภาพในการทำงานของแรงงานนอกระบบของชุมชนมุสลิม ประชากรที่ใช้ในการศึกษาวิจัยครั้งนี้ คือ ประชาชนมุสลิมที่อาศัยอยู่ในเขตพื้นที่ตำบลบางปูที่ประกอบอาชีพอิสระและเป็นแรงงานนอกระบบประกันสังคม จำนวนทั้งสิ้น 760 คน สุ่มตัวอย่างแบบเป็นระบบได้ขนาดตัวอย่าง 200 คน วิเคราะห์ข้อมูลโดยใช้สถิติเชิงพรรณนา ได้แก่ การแจกแจงความถี่ ร้อยละ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน ค่าสูงสุด และค่าต่ำสุด สถิติเชิงอนุมาน ได้แก่ 95%CI of mean ผลการศึกษาพบว่า สัดส่วนภาวะการเจ็บป่วยในรอบ 1 ปีที่ผ่านมา จำแนกตามเพศพบว่า กลุ่มตัวอย่างที่เคยเจ็บป่วยในรอบปีที่ผ่านมาเป็นเพศชาย ร้อยละ 49.5 (95%CI: 38.9 ถึง 59.9) เป็นเพศหญิง ร้อยละ 45.2 (95%CI: 35.9 ถึง 54.3) กลุ่มตัวอย่างที่เคยเจ็บป่วยในรอบปีที่ผ่านมามีอายุไม่เกิน 45 ปี ร้อยละ 46.4 (95%CI: 36.4 ถึง 56.3) อายุมากกว่า 45 ปีขึ้นไป ร้อยละ 47.6 (95%CI: 37.9 ถึง57.2) มีอายุเฉลี่ย 45.7 ปี (S.D.=11.2) มีอาชีพหลักค้าขายมากที่สุด ร้อยละ 64 มีสถานะของอาชีพหลักเป็นเจ้าของกิจการ ร้อยละ 70.0 กลุ่มตัวอย่างมีความเสี่ยงต่อสุขภาพในการทำงานในระดับสูง ได้แก่ ด้านปัญหาระดับความรุนแรงในการทำงาน มากที่สุด ร้อยละ 60 รองลงมาด้านพฤติกรรมความปลอดภัยในการทำงาน ร้อยละ 57.0 กว่าร้อยละ 20 ที่ไม่ทราบว่าตนเองนั้นมีโรคประจำตัวหรือไม่และกลุ่มตัวอย่าง ร้อยละ 18 เป็นโรคความดันโลหิตสูงกว่าครึ่งที่สภาพการทำงานมีปัญหาต่อสุขภาพ ได้แก่ ยกของหนัก หรือทำงานในท่าทางที่ทำให้เกิดอาการปวดเมื่อย ร้อยละ 75.0 สัมผัสแหล่งความร้อนหรือทำงานกลางแจ้ง ร้อยละ 54.5 และบริเวณที่ทำงานมีฝุ่นละออง ร้อยละ 53.0 ตามลำดับ หน่วยงานที่เกี่ยวข้องควรให้ความสำคัญด้านสุขภาพและสวัสดิการในการทำงานของแรงงานนอกระบบชุมชนมุสลิม คำสำคัญ: ความเสี่ยงต่อสุขภาพ แรงงานนอกระบบ ชุมชนมุสลิม This is a cross-sectional descriptive research which aimed to assess health risk in working of the informal workers in Muslim community. The population of the study was 760 Muslims who lived in Bangpoo district, worked freelance, and were not insured in the social insurance system. 200 participants were selected using systematic sampling. The data was analyzed using descriptive statistics which were frequency distribution, percentage, mean, standard deviation, and minimum and maximum values. The inferential statistics was 95% CI mean. The results of the study in the proportion of illness in the previous year round classified according to genders was found that 49.5 percent of the male participants were sick (95%CI: 38.9-59.9) while there were 45.2 percent of female participants who got ill (95%:35.9 to 54.3). 46.4 percent of these participants were less than 45 years old (95%CI: 36.4 to 56.3) while the other 45.2 percent were more than 45 years old (95%CI: 37.9 to 57.2). The average year of age was 45.7 (S.D.=11.2). Trading was the most popular main occupation which accounted for 64 percent. 70 percent of group were business owners. The samplings had a high health risk in working. To illustrate, the most risk involved the degree of violence in working. It accounted for 60 percent. The second most risk concerned with safety behavior in working. This accumulated for 60 percent. More than 20 percent did not realized if they had congenital diseases or not and 18 percent of the samplings had high blood pressure. More than half of the participants had a bad working condition that affected their health such as lifting heavy objects or working in the manners which could cause pains and aches, 75.0 percent; touching heat sources or working outdoor, 54.5 percent; and working in dusty areas, 53 percent, respectively. Therefore, related institutes should give priority to health and welfare in working of Muslim informal workers. Keywords: Health Risk, Informal workers, Muslim community